Boycott Appeals and Local Purchase Intentions: The Role of Campaign Intensity in Indonesia’s Consumer Behavior - Ricky Angga Ariska; Fadilla Purwitasari; Evianah Evianah (International Journal of Management Science and Information Technology, 2026)
This study employs a quantitative, cross-sectional explanatory design to assess whether boycott appeals against Israel-affiliated products translate into interest in purchasing local products in Indonesia. Data were collected through an online, closed-ended Likert-scale survey distributed via Google Forms using snowball sampling among adult consumers aware of boycott campaigns. The model was estimated using partial least squares structural equation modeling (PLS-SEM) with reliability/validity assessment and bootstrapping (5,000 resamples). Results indicate that boycott campaign intensity does not significantly predict boycott intention or buy-local interest, while attitudes and subjective norms increase boycott intention but do not strengthen buy-local interest (attitude shows a negative direct effect). Animosity significantly increases both boycott intention and buy-local interest, whereas boycott intention does not significantly predict buy-local interest and does not mediate antecedent effects. The findings imply that effective “buy local” outcomes require credible moral-emotional framing and accessible substitutes beyond exposure-driven campaigning.